2019
DOI: 10.1016/j.nlm.2019.107041
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in appetitive trace conditioning and novel object recognition procedures

Abstract: HighlightsLongitudinal study of middle age in the rat with matched younger control cohort.Appetitive trace conditioning and novel object recognition tests of working memory.Transient between-groups working memory impairments aged 12 compared with 2 months.Object exploration reduced with age but working memory recovered.Object exploration and ITI nosepoking showed some correlation with 5-HIAA/5-HT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…However, the performance was not different from the chance at 18 months, indicating impaired recognition, despite no age-related difference in time exploring the objects. Similarly, other longitudinal studies find improvements due to previous training (Chiquita et al, 2019;Marshall et al, 2019). Thus, previous experience influences performance possibly due to positive transfer.…”
Section: Perirhinal Cortex Based Tasks Novel Object Recognitionmentioning
confidence: 76%
“…However, the performance was not different from the chance at 18 months, indicating impaired recognition, despite no age-related difference in time exploring the objects. Similarly, other longitudinal studies find improvements due to previous training (Chiquita et al, 2019;Marshall et al, 2019). Thus, previous experience influences performance possibly due to positive transfer.…”
Section: Perirhinal Cortex Based Tasks Novel Object Recognitionmentioning
confidence: 76%
“…In a longitudinal study of ageing male Wistar rats, we found that object exploration was overall reduced in middle aged rats and was further reduced when the rats were 6 months older. However, an initial NOR impairment (seen at a 24hr but not at a 10 min retention interval) showed recovery at the second point of testing [20] . These findings suggest that any strain differences by age seen cross-sectionally could similarly be overcome with enriched housing conditions and regular handling.…”
Section: Discussionmentioning
confidence: 89%
“…The Novel Object Recognition (NOR) test was carried out to evaluate recognition memory (non-spatial working memory) [30,31]. The NOR test was performed according to a previously published method [32].…”
Section: Novel Object Recognition Testmentioning
confidence: 99%